Increasing Understanding of Family Members We On Children In Early Childhood Education Aisyiah Wirogunan Through Learning Method Game Guess My Family - Suyahman, Suyahman (Indonesian Journal of Early Childhood Education Studies, 2016)
Motivating the selection of the title of this study is the existence of a fact that the majority of children in Early Childhood Education Aisyiah when asked by the teacher about the identity of family members generally confused or do not know even cried. This condition is scientifically interesting to examine why this is so. I was thinking whether the way the teacher when ask less humanist, or the language used by teachers are poorly understood or ask when the time is not quite right. My mind ultimately boils down to the method used by the teacher is less precise, that's why I made the decision to examine scientifically by choosing a method of game "guessed my family members" can make it easier to understand a family member. The purpose of this study is to describe an improved understanding of family members through the use of Learning Method Game Guess My Family. This research is qualitative research with research subjects: children Aisyiah Wirogunan Early Childhood Education, and the object of research: Understanding Family Members We On Children In Early Childhood Education Aisyiah Wirogunan. Source informant were teachers and children Didik In Childhood Education Disi Aisyiah Wirogunan, Kartasura. Data collection methods used were interviews, observation and documentation. To obtain the validity of the data used triangulation method, and for the sake of data analysis used descriptive data analysis techniques interactive that includes four stages: data collection, data verification, exposure data and drawing conclusions The results empirically showed that before the teacher using the game of guessing my family members, children in early childhood education Aisyiah Wirogunan, Kartasura when asked who the members kelurganya, children generally can not answer, there is no idea, there are confused and even there crying. Having used method of guessing game of my family members there are significant changes that the child can answer with a firm, precise and fast even dare to tell the class about their family members.